PATH PLANNING OF ROBOT IN STATIC ENVIRONMENT USING GENETIC ALGORITHM (GA) TECHNIQUE - Parvez, Waghoo; Dhar, Sonal (International journal of advances in engineering and technology, 2013)
This paper presents the application of genetic algorithm in path planning for a static warehouse environment with multiple objectives. It quantitatively evaluates the performance of genetic algorithm which is used for a variety of applications. In a warehouse equipped with robot for material handling and transportation, the path taken by the robot plays an important role as it defines the time required for transportation. Nowadays, transportation cost should also be minimized to reduce the cost of the product, which can be minimized by optimizing the path for transportation. GA is applied for optimizing the path of a robot in warehouses for material handling with a predetermined location as a starting point to reach a pre-determined goal. The program has been developed in C++ language. The technique is able to generate feasible, stable and optimal sequence.